Composition, microstructure and mechanical properties of cBN-based composites sintered with AlN- Al- Ni binder. Issue 14 (1st October 2018) - Li, Liqiang; Zhao, Yabo; Sun, Kun; Ji, Huanli; Feng, Dandan; Li, Zhihong
Abstract: Cubic boron nitride (cBN)-based composites were fabricated using AlN-Al-Ni binders at high pressure and high temperature (HPHT). Effects of binder content and temperature on phase composition, microstructure and mechanical properties of cBN-based composites were investigated. Abrasive ratio was measured using a new method. Almost all Al reacted with cBN during sintering, resulting in AlN as well as AlB2 phases, while remaining Al and Ni formed intermetallic compounds. At 1500 °C, the reaction reached its maximum. Excellent relative density, flexural strength and fracture toughness of composites, sintered with 17 wt% binder, were 99.6%, 661 MPa and 7.19 MPa m 1/2, respectively. However, the optimum value of hardness and abrasive ratio of composites at binder content of 13 wt% were 47.92 GPa and 2.99, respectively.